Preparation method of high-temperature-resistant composite material for battery pack

CN122878097APending Publication Date: 2026-10-09HUA YIN NAI HUO CAI LIAO YOU XIAN GONG SI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611399196.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明提供一种电池包用耐高温复合材料的制备方法,解决现有技术中,玻璃纤维在蒸压养护的高温强碱水热环境中易发生碱蚀劣化,导致复合材料在热暴露后抗压强度保留率低的技术问题

Benefits of technology

本发明通过将改性玻璃纤维与钙质浆料、硅质浆料等混合压滤并蒸压养护,制得一种电池包用耐高温复合材料。改性玻璃纤维制备时,通过TEOS与四丙醇锆的水解缩合以及热处理,在玻璃纤维上形成以Zr-O-Zr键为主、含有少量Zr-O-Si键的阻隔层,Zr-O-Zr键在高温强碱下稳定,使阻隔层在蒸压养护时维持覆盖玻璃纤维的状态,降低玻璃纤维因碱蚀而导致的强度损失,使得玻璃纤维不易在基体非均匀受热所产生的热应力作用下发生断裂,抑制基体微裂纹萌生与扩展,同时Zr-O-Si键断裂并溶出硅氧组分,增加阻隔层表面粗糙度,使得改性玻璃纤维与基体形成机械互锁,抑制微裂纹的连通和扩大,提升复合材料在热暴露后的抗压强度保留率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878097A_ABST
    Figure CN122878097A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of preparation of hard silicon calcium plate, and particularly relates to a preparation method of high-temperature-resistant composite material for battery pack, comprising the following steps: dispersing glass fibers in an ethanol solution, adding a barrier layer precursor solution after adjusting pH value, mixing and reacting, drying and heat treating to obtain modified glass fibers, mixing the modified glass fibers with calcareous slurry, siliceous slurry and deionized water, performing autoclave curing after forming a blank, and drying to obtain the high-temperature-resistant composite material for battery pack; the barrier layer precursor solution is prepared by mixing and reacting TEOS and acidic ethanol solution, and then adding zirconium-containing chelate solution for mixing and reaction; the zirconium-containing chelate solution is prepared by reacting zirconium tetrapropoxide and acetylacetone. The present application can solve the technical problem that glass fibers are prone to alkali corrosion and degradation in the high-temperature strong-alkali hydrothermal environment during autoclave curing in the prior art, resulting in low compressive strength retention rate of the composite material after thermal exposure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hard silica calcium stone slab preparation technology, and particularly relates to a method for preparing a high-temperature resistant composite material for battery packs. Background Technology

[0002] Hard calcium silicate slabs, with a continuous hard calcium silicate whisker network as their matrix, possess low thermal conductivity and are commonly used in battery packs as thermal insulation between cells, modules, and between cells and the casing to delay or block the spread of heat during thermal runaway. Under actual high-temperature conditions, the slabs are often subjected to non-uniform heating, creating a temperature gradient between the heated and unheated surfaces. This results in inconsistent thermal expansion on both sides of the slab, generating thermal stress within the matrix. When this local thermal stress exceeds the matrix's bearing capacity, microcracks are induced within the matrix, leading to a low retention rate of compressive strength after high-temperature exposure.

[0003] Chinese patent application CN104250089A discloses a process for preparing lightweight, high-temperature resistant, hard calcium silicate-type thermal insulation material, including the following steps: mixing calcium oxide, silicon dioxide, and water, adding cotton fiber, glass fiber, and silica sol to form a slurry, pressing it into shape, steam curing, and drying to obtain the hard calcium silicate thermal insulation material. In the aforementioned application, glass fiber is added during the board preparation process. Glass fiber can inhibit the initiation and propagation of microcracks under the thermal stress generated by non-uniform heating of the matrix through bridging, frictional energy dissipation, and stress dispersion. However, in the aforementioned application, the glass fiber is directly exposed to the high-temperature, strong alkaline hydrothermal environment formed by steam curing. Its main component, silicon dioxide, reacts chemically with the alkaline medium, causing alkaline corrosion of the glass fiber, reducing its mechanical strength. The alkaline-corroded glass fiber is prone to breakage under thermal stress, making it difficult to effectively inhibit the initiation and propagation of microcracks, resulting in a low retention rate of compressive strength after heat exposure. Summary of the Invention

[0004] This invention provides a method for preparing high-temperature resistant composite materials for battery packs, solving the technical problem in the prior art that glass fibers are prone to alkaline corrosion and deterioration in the high-temperature and strong alkaline hydrothermal environment of autoclaving, resulting in low compressive strength retention rate of composite materials after heat exposure.

[0005] To solve the above problems, the present invention adopts the following technical solution: A method for preparing a high-temperature resistant composite material for a battery pack includes the following steps: S1. Disperse glass fibers in an ethanol solution, adjust the pH value, add a barrier layer precursor solution, mix and react, dry and heat treat to obtain modified glass fibers. S2. Mix calcium slurry, silica slurry, deionized water and modified glass fiber, dehydrate to form a green body, then steam-press curing and drying to obtain a high-temperature resistant composite material for battery packs. The barrier layer precursor solution is prepared by mixing and reacting TEOS (tetraethyl orthosilicate) and an acidic ethanol solution, then adding a zirconium-containing chelate solution and reacting to obtain the barrier layer precursor solution; the zirconium-containing chelate solution is prepared by reacting tetrapropionitrile and acetylacetone.

[0006] This invention produces a high-temperature resistant composite material for battery packs (hereinafter referred to as the composite material) by mixing modified glass fibers with calcareous slurry, silica slurry, etc., forming a preform, and then steam-curing it. During the preparation of the modified glass fibers, a zirconium-rich gel layer is formed on the outside of the glass fibers through the condensation crosslinking of TEOS and zirconium tetrapropoxide hydrolysate. After heat treatment, the zirconium-rich gel layer undergoes further condensation crosslinking to form a barrier layer dominated by Zr-O-Zr bonds with a small amount of Zr-O-Si bonds, thus obtaining the modified glass fibers.

[0007] During autoclaving, calcium ions and silicate ions form a continuous hard silica-calcium silicate whisker network matrix (hereinafter referred to as the matrix) in a high-temperature, strong alkaline environment. The Zr-O-Zr bonds in the barrier layer are highly stable and have a low fracture rate under high-temperature, strong alkaline conditions, allowing the barrier layer to remain continuously covering the glass fiber surface. This reduces direct contact between the glass fiber and the high-concentration alkaline solution, minimizing strength loss caused by alkaline etching. It also makes the fiber less prone to fracture under thermal stress caused by non-uniform heating of the matrix, inhibiting the initiation and propagation of microcracks in the matrix and improving the compressive strength retention rate of the composite material after heat exposure. Under high-temperature, strong alkaline conditions, the Zr-O-Si bonds in the barrier layer are preferentially attacked and broken by hydroxide ions, causing the silicon-oxygen components to dissolve. This increases the surface roughness of the barrier layer, which is beneficial for mechanical interlocking between the matrix and the modified glass fiber. The mechanical interlocking interface can increase the resistance to microcrack propagation, inhibit the connection and expansion of microcracks, and further improve the compressive strength retention rate of the composite material after heat exposure.

[0008] Furthermore, the barrier layer precursor solution is prepared by adding acetic acid solution dropwise to an 84-86 wt% ethanol solution to adjust the pH to 4-5, adding TEOS and reacting for 1-1.5 h, then slowly adding a zirconium-containing chelate solution under continuous stirring, and reacting for 40-50 min to obtain the barrier layer precursor solution; the zirconium-containing chelate solution is prepared by mixing and reacting tetrapropoxide zirconium and acetylacetone in an inert atmosphere for 30-40 min.

[0009] The hydrolytic activity of zirconium tetrapropoxide in the ethanol-water system is reduced by chelating acetylacetone with zirconium tetrapropoxide. TEOS is first pre-hydrolyzed in an acidic ethanol-water system to form an oligomeric silica sol containing silanol groups. Then, the zirconium-containing chelate solution is slowly added under continuous stirring to allow the zirconium hydroxyl groups and silanol groups to co-condense and form Zr-O-Si bonds, reducing local zirconium-rich agglomeration. This is beneficial for forming a continuous and uniform zirconium-rich gel layer on the outside of the glass fiber, reducing the risk of defects such as cracking and peeling of the barrier layer due to uneven shrinkage during subsequent drying and heat treatment, reducing direct contact between the glass fiber and high-concentration alkaline solution, and effectively preserving the mechanical strength of the glass fiber.

[0010] Further, in step S1, glass fibers are dispersed in a 91-93 wt% ethanol solution, and acetic acid solution is added dropwise to adjust the pH to 4-5. The barrier layer precursor solution is slowly added under continuous stirring, and the reaction is carried out for 1-1.5 hours. The temperature is then raised to 78-80℃ and reacted for 3-4 hours. After filtration and vacuum drying, the mixture is heat-treated at 450-460℃ for 2-2.5 hours, then heat-treated at 550-560℃ for 3-4 hours, and finally cooled to obtain modified glass fibers. The zirconium content in the glass fibers is 14%-15%.

[0011] The glass fiber used is zirconium-containing alkali-resistant glass fiber, which can maintain the stability of fiber morphology and structure during heat treatment at 550-560℃, reducing the risk of cracking of the barrier layer caused by thermal shrinkage or deformation of the glass fiber, and is conducive to maintaining the continuity of the barrier layer. Under the condition of 550-560℃, the zirconium-rich gel layer further condenses and the organic components are fully decomposed, reducing the internal micropores and defects of the barrier layer, improving the density of the barrier layer, and reducing the penetration and erosion rate of alkali solution to the barrier layer in the strong alkaline hydrothermal environment of subsequent autoclaving, shortening the direct contact time between high concentration alkali solution and the glass fiber surface, and preserving the mechanical strength of the glass fiber.

[0012] Furthermore, in step S1, after heat treatment at 550-560℃ for 3-4 hours and cooling, plasma treatment is performed using a mixture of oxygen and argon gas. Then, the mixture is dispersed in an ethanol solution, the pH value is adjusted, and a coating layer precursor solution is added for mixing and reaction. After drying and heat treatment, modified glass fiber is obtained. The coating layer precursor solution is prepared by mixing and reacting TEOS and acidic ethanol solution.

[0013] Further, in step S1, oxygen and argon are mixed in a volume ratio of (1-1.2):1 and used as working gas. After plasma treatment for 15-17 minutes under working gas flow rate of 40-50 sccm and radio frequency power of 75-80W, the mixture is dispersed in a 91-93wt% ethanol solution. Acetic acid solution is added dropwise to adjust the pH value to 4-5. The coating layer precursor solution is slowly added under continuous stirring and reacted for 1-1.5 hours. The temperature is raised to 78-80℃ and reacted for 3-4 hours. The mixture is filtered, dried under reduced pressure, and then heat-treated at 450-460℃ for 3-4 hours. After cooling, modified glass fiber is obtained.

[0014] Plasma treatment with a mixture of oxygen and argon gases increases the hydroxyl density on the surface of the barrier layer, which facilitates the condensation of TEOS hydrolysis products outside the barrier layer. After heat treatment at 450-460℃, a coating layer with Si-O-Si bonds as the main body is formed outside the barrier layer. This coating layer is mainly composed of amorphous silica, which can preferentially dissolve over crystalline quartz powder in the early stage of autoclaving, forming a locally high concentration of silicate ions around the modified glass fiber. This promotes the nucleation of calcium silicate on the surface of the modified glass fiber, enhances the mechanical interlock between the modified glass fiber and the matrix, further inhibits the connection and expansion of microcracks in the matrix under thermal stress, and improves the compressive strength retention rate of the composite material after heat exposure.

[0015] Furthermore, the coating layer precursor solution is prepared by adding acetic acid solution dropwise to an 84-86 wt% ethanol solution to adjust the pH value to 4-5, adding TEOS and reacting for 2-2.5 h to obtain the coating layer precursor solution.

[0016] Furthermore, in step S2, the calcium slurry, silica slurry, modified glass fiber and deionized water are mixed evenly, pressed into a blank, and then steam-cured at 190-195℃ and 1.3-1.4MPa for 12-14 hours, dried at 130-140℃ for 6-8 hours, and cooled to obtain a high-temperature resistant composite material for battery packs.

[0017] Furthermore, the calcium slurry is prepared by reacting calcium oxide with deionized water, and the silica slurry is prepared by mixing quartz powder with deionized water.

[0018] Furthermore, the high-temperature resistant composite material for the battery pack comprises the following raw materials in parts by weight: 910-920 parts of calcium slurry, 918-925 parts of silica slurry, 600-610 parts of deionized water, and 27-30 parts of modified glass fiber; the modified glass fiber comprises the following raw materials in parts by weight: 50-60 parts of glass fiber and 190-195 parts of barrier layer precursor liquid.

[0019] Furthermore, the calcium slurry is prepared by mixing and reacting 180-184 parts by weight of calcium oxide and 750-760 parts by weight of deionized water; the silica slurry is prepared by mixing 188-192 parts by weight of quartz powder and 745-755 parts by weight of deionized water; the barrier layer precursor liquid comprises the following raw materials in parts by weight: 73-77 parts of zirconium tetrapropoxide, 49-52 parts of acetylacetone, 7-8 parts of TEOS, and 140-150 parts of 84-86 wt% ethanol solution; the modified glass fiber further comprises 90-95 parts by weight of coating layer precursor liquid, which comprises the following raw materials in parts by weight: 30-35 parts of TEOS and 80-90 parts of 84-86 wt% ethanol solution.

[0020] By controlling the mass ratio of zirconium tetrapropoxide to TEOS, it is beneficial for the barrier layer to have a continuous Zr-O-Zr network as the main body, with Zr-O-Si bonds distributed in a small amount and in an isolated and dispersed form. This allows the silicon-oxygen components to dissolve and form isolated micropores. On the one hand, this increases the surface roughness of the barrier layer, which is beneficial for forming a mechanical interlock with the substrate. On the other hand, it avoids the formation of erosion channels that penetrate the barrier layer, reduces the direct contact between the glass fiber and the high-concentration alkaline solution, and effectively preserves the mechanical strength of the glass fiber.

[0021] The present invention has the following beneficial effects: This invention produces a high-temperature resistant composite material for battery packs by mixing modified glass fibers with calcium slurry, silica slurry, etc., pressing and filtering, and then steam curing. During the preparation of the modified glass fibers, a barrier layer is formed on the glass fibers through hydrolysis and condensation of TEOS and zirconium tetrapropoxide, followed by heat treatment. This barrier layer is mainly composed of Zr-O-Zr bonds and contains a small amount of Zr-O-Si bonds. The Zr-O-Zr bonds are stable under high temperature and strong alkali conditions, ensuring that the barrier layer maintains its covering state on the glass fibers during steam curing. This reduces the strength loss of the glass fibers due to alkali corrosion, making the glass fibers less prone to breakage under thermal stress caused by non-uniform heating of the matrix. It also inhibits the initiation and propagation of microcracks in the matrix. Simultaneously, the breakage of Zr-O-Si bonds and the dissolution of silicon-oxygen components increase the surface roughness of the barrier layer, creating a mechanical interlock between the modified glass fibers and the matrix. This further inhibits the connection and propagation of microcracks, improving the compressive strength retention rate of the composite material after heat exposure. Attached Figure Description

[0022] Figure 1 The infrared spectrum of the modified glass fiber prepared in Example 4; Figure 2 The image shows the infrared spectrum of the modified glass fiber prepared in Example 3. Detailed Implementation

[0023] Example 1 Under nitrogen protection, 77g of tetrazirconium propoxide and 51g of acetylacetone were mixed and stirred at 300rpm for 40min to obtain a zirconium-containing chelate solution. 5wt% acetic acid solution was added dropwise to 150g of 86wt% ethanol solution to adjust the pH to 5. 8g of TEOS was added and stirred at 300rpm for 1.5h. The zirconium-containing chelate solution was slowly added dropwise under stirring at 500rpm. After the addition was complete, the mixture was stirred at 300rpm for 45min to obtain the barrier layer precursor solution.

[0024] 55g of glass fiber (12mm in length, 10μm in diameter of a single filament, and 15% ZrO2 content) was added to 600g of 91wt% ethanol solution and ultrasonically dispersed at 100W for 20min. The pH was adjusted to 4.5 by adding 5wt% acetic acid solution dropwise. 195g of barrier layer precursor solution was slowly added dropwise under stirring at 400rpm. After the addition was complete, the mixture was stirred at 300rpm for 1.2h, heated to 78℃, refluxed at 150rpm for 4h, filtered, dried at 50℃ and 10kPa for 5h, kept at 450℃ for 2.5h, heated to 550℃ and kept at 550℃ for 4h, and cooled to room temperature to obtain modified glass fiber.

[0025] 180g of calcium oxide was slowly mixed with 750g of deionized water and stirred at 300rpm for 45min to obtain a calcium slurry. 190g of quartz powder (3μm particle size) was mixed with 745g of deionized water and stirred at 900rpm for 30min to obtain a silica slurry. 910g of calcium slurry, 918g of silica slurry, and 600g of deionized water were mixed and stirred at 1000rpm for 10min. 30g of modified glass fiber was slowly added while stirring at 700rpm. After the addition was complete, the mixture was stirred at 700rpm for 30min, filtered to remove water, and formed a green body. The green body was then steam-cured at 192℃ and 1.35MPa for 13h, dried at 140℃ for 6h, and cooled to room temperature to obtain a high-temperature resistant composite material for battery packs.

[0026] Example 2 Under nitrogen protection, 75g of tetrazirconium tetrapropoxide and 52g of acetylacetone were mixed and stirred at 300rpm for 35min to obtain a zirconium-containing chelate solution. 5wt% acetic acid solution was added dropwise to 145g of 84wt% ethanol solution to adjust the pH to 4.5. 7.5g of TEOS was added and stirred at 300rpm for 1.3h. The zirconium-containing chelate solution was slowly added dropwise under stirring at 500rpm. After the addition was complete, the mixture was stirred at 300rpm for 50min to obtain the barrier layer precursor solution.

[0027] 60g of glass fiber (12mm in length, 10μm in diameter of a single filament, and 14% ZrO2 content) was added to 600g of 93wt% ethanol solution and ultrasonically dispersed at 100W for 20min. The pH was adjusted to 5 by adding 5wt% acetic acid solution dropwise. 193g of barrier layer precursor solution was slowly added dropwise under stirring at 400rpm. After the addition was complete, the mixture was stirred at 300rpm for 1.5h, heated to 79℃, refluxed at 150rpm for 3.5h, filtered, dried at 50℃ and 10kPa for 5h, kept at 455℃ for 2.3h, heated to 555℃ and kept at 555℃ for 3.5h, and cooled to room temperature to obtain modified glass fiber.

[0028] 182g of calcium oxide was slowly mixed with 755g of deionized water and stirred at 300rpm for 45min to obtain a calcium slurry. 188g of quartz powder (3μm particle size) was mixed with 755g of deionized water and stirred at 900rpm for 30min to obtain a silica slurry. 915g of calcium slurry, 925g of silica slurry, and 605g of deionized water were mixed and stirred at 1000rpm for 10min. 28g of modified glass fiber was slowly added while stirring at 700rpm. After addition, the mixture was stirred at 700rpm for 30min, filtered to remove water, and formed a green body. The green body was then steam-cured at 195℃ and 1.4MPa for 14h, dried at 135℃ for 7h, and cooled to room temperature to obtain a high-temperature resistant composite material for battery packs.

[0029] Example 3 Under nitrogen protection, 73g of zirconium tetrapropoxide and 49g of acetylacetone were mixed and stirred at 300rpm for 30min to obtain a zirconium-containing chelate solution. 5wt% acetic acid solution was added dropwise to 140g of 85wt% ethanol solution to adjust the pH to 4. 7g of TEOS was added and stirred at 300rpm for 1h. The zirconium-containing chelate solution was slowly added dropwise under stirring at 500rpm. After the addition was completed, the mixture was stirred at 300rpm for 40min to obtain the barrier layer precursor solution.

[0030] 50g of glass fiber (12mm in length, 10μm in diameter of a single filament, and 14.5% ZrO2 content) was added to 600g of 92wt% ethanol solution and ultrasonically dispersed at 100W for 20min. The pH was adjusted to 4 by adding 5wt% acetic acid solution dropwise. 190g of barrier layer precursor solution was slowly added dropwise under stirring at 400rpm. After the addition was complete, the mixture was stirred at 300rpm for 1h, heated to 80℃, refluxed at 150rpm for 3h, filtered, dried at 50℃ and 10kPa for 5h, kept at 460℃ for 2h, heated to 560℃ and kept at 560℃ for 3h, and cooled to room temperature to obtain modified glass fiber.

[0031] 184g of calcium oxide was slowly mixed with 760g of deionized water and stirred at 300rpm for 45min to obtain a calcium slurry. 192g of quartz powder (3μm particle size) was mixed with 750g of deionized water and stirred at 900rpm for 30min to obtain a silica slurry. 920g of calcium slurry, 922g of silica slurry, and 610g of deionized water were mixed and stirred at 1000rpm for 10min. 27g of modified glass fiber was slowly added while stirring at 700rpm. After addition, the mixture was stirred at 700rpm for 30min, filtered to remove water, and formed a green body. The green body was then steam-cured at 190℃ and 1.3MPa for 12h, dried at 130℃ for 8h, and cooled to room temperature to obtain a high-temperature resistant composite material for battery packs.

[0032] Example 4 Under nitrogen protection, 73g of zirconium tetrapropoxide and 49g of acetylacetone were mixed and stirred at 300rpm for 30min to obtain a zirconium-containing chelate solution. 5wt% acetic acid solution was added dropwise to 140g of 85wt% ethanol solution to adjust the pH to 4. 7g of TEOS was added and stirred at 300rpm for 1h. The zirconium-containing chelate solution was then slowly added dropwise under stirring at 500rpm. After the addition was complete, the mixture was stirred at 300rpm for 40min to obtain the barrier layer precursor solution. 5wt% acetic acid solution was added dropwise to 85g of 85wt% ethanol solution to adjust the pH to 4. 32g of TEOS was added and stirred at 300rpm for 2.3h to obtain the coating layer precursor solution.

[0033] 50g of glass fiber (12mm in length, 10μm in diameter of a single filament, and 14.5% ZrO2 content) was added to 600g of 92wt% ethanol solution and ultrasonically dispersed at 100W for 20min. The pH was adjusted to 4 by adding 5wt% acetic acid solution dropwise. 190g of barrier layer precursor solution was slowly added dropwise while stirring at 400rpm. After addition, the mixture was stirred at 300rpm for 1h, heated to 80℃, refluxed at 150rpm for 3h, filtered, dried at 50℃ and 10kPa for 5h, heat-treated at 460℃ for 2h, and heat-treated at 560℃ for 3h. After cooling to room temperature, the mixture was placed in a plasma generator, where oxygen and argon were mixed at a 1:1 volume ratio as the working gas. Plasma treatment was performed for 17 min under conditions of gas flow rate of 40 sccm and radio frequency power of 80 W. After removal, the solution was added to 600 g of 92 wt% ethanol solution and ultrasonically dispersed at 80 W for 15 min. The pH value was adjusted to 4 by adding 5 wt% acetic acid solution dropwise. 90 g of coating layer precursor solution was slowly added dropwise under stirring at 450 rpm. After the addition was completed, the solution was stirred at 300 rpm for 1 h, heated to 80 °C, refluxed at 150 rpm for 3 h, filtered, dried in an environment of 50 °C and 10 kPa for 5 h, kept at 460 °C for 3 h, and cooled to room temperature to obtain modified glass fiber.

[0034] 184g of calcium oxide was slowly mixed with 760g of deionized water and stirred at 300rpm for 45min to obtain a calcium slurry. 192g of quartz powder (3μm particle size) was mixed with 750g of deionized water and stirred at 900rpm for 30min to obtain a silica slurry. 920g of calcium slurry, 922g of silica slurry, and 610g of deionized water were mixed and stirred at 1000rpm for 10min. 27g of modified glass fiber was slowly added while stirring at 700rpm. After addition, the mixture was stirred at 700rpm for 30min, filtered to remove water, and formed a green body. The green body was then steam-cured at 190℃ and 1.3MPa for 12h, dried at 130℃ for 8h, and cooled to room temperature to obtain a high-temperature resistant composite material for battery packs.

[0035] Example 5 Under nitrogen protection, 73g of zirconium tetrapropoxide and 49g of acetylacetone were mixed and stirred at 300rpm for 30min to obtain a zirconium-containing chelate solution. 5wt% acetic acid solution was added dropwise to 140g of 85wt% ethanol solution to adjust the pH to 4. 7g of TEOS was added and stirred at 300rpm for 1h. The zirconium-containing chelate solution was slowly added dropwise under stirring at 500rpm. After the addition was complete, the mixture was stirred at 300rpm for 40min to obtain the barrier layer precursor solution. 5wt% acetic acid solution was added dropwise to 80g of 84wt% ethanol solution to adjust the pH to 4.5. 35g of TEOS was added and stirred at 300rpm for 2h to obtain the coating layer precursor solution.

[0036] 50g of glass fiber (12mm in length, 10μm in diameter of a single filament, and 14.5% ZrO2 content) was added to 600g of 92wt% ethanol solution and ultrasonically dispersed at 100W for 20min. The pH was adjusted to 4 by adding 5wt% acetic acid solution dropwise. 190g of barrier layer precursor solution was slowly added dropwise while stirring at 400rpm. After addition, the mixture was stirred at 300rpm for 1h, heated to 80℃, refluxed at 150rpm for 3h, filtered, dried at 50℃ and 10kPa for 5h, heat-treated at 460℃ for 2h, and heat-treated at 560℃ for 3h. After cooling to room temperature, the mixture was placed in a plasma generator. Oxygen and argon were mixed at a volume ratio of 11:10 as the working gas. Plasma treatment was performed for 16 min at a flow rate of 45 sccm and a radio frequency power of 77 W. The solution was then removed and added to 600 g of 93 wt% ethanol solution. The solution was ultrasonically dispersed at 80 W for 15 min. The pH was adjusted to 4.5 by adding 5 wt% acetic acid solution. 95 g of coating layer precursor solution was slowly added dropwise while stirring at 450 rpm. After the addition was complete, the solution was stirred at 300 rpm for 1.2 h, heated to 79 °C, refluxed at 150 rpm for 3.5 h, filtered, dried at 50 °C and 10 kPa for 5 h, and kept at 450 °C for 4 h. The solution was then cooled to room temperature to obtain modified glass fiber.

[0037] 184g of calcium oxide was slowly mixed with 760g of deionized water and stirred at 300rpm for 45min to obtain a calcium slurry. 192g of quartz powder (3μm particle size) was mixed with 750g of deionized water and stirred at 900rpm for 30min to obtain a silica slurry. 920g of calcium slurry, 922g of silica slurry, and 610g of deionized water were mixed and stirred at 1000rpm for 10min. 27g of modified glass fiber was slowly added while stirring at 700rpm. After addition, the mixture was stirred at 700rpm for 30min, filtered to remove water, and formed a green body. The green body was then steam-cured at 190℃ and 1.3MPa for 12h, dried at 130℃ for 8h, and cooled to room temperature to obtain a high-temperature resistant composite material for battery packs.

[0038] Example 6 Under nitrogen protection, 73g of zirconium tetrapropoxide and 49g of acetylacetone were mixed and stirred at 300rpm for 30min to obtain a zirconium-containing chelate solution. 5wt% acetic acid solution was added dropwise to 140g of 85wt% ethanol solution to adjust the pH to 4. 7g of TEOS was added and stirred at 300rpm for 1h. The zirconium-containing chelate solution was slowly added dropwise under stirring at 500rpm. After the addition was complete, the mixture was stirred at 300rpm for 40min to obtain the barrier layer precursor solution. 5wt% acetic acid solution was added dropwise to 90g of 86wt% ethanol solution to adjust the pH to 5. 30g of TEOS was added and stirred at 300rpm for 2.5h to obtain the coating layer precursor solution.

[0039] 50g of glass fiber (12mm in length, 10μm in diameter of a single filament, and 14.5% ZrO2 content) was added to 600g of 92wt% ethanol solution and ultrasonically dispersed at 100W for 20min. The pH was adjusted to 4 by adding 5wt% acetic acid solution dropwise. 190g of barrier layer precursor solution was slowly added dropwise while stirring at 400rpm. After addition, the mixture was stirred at 300rpm for 1h, heated to 80℃, refluxed at 150rpm for 3h, filtered, dried at 50℃ and 10kPa for 5h, heat-treated at 460℃ for 2h, and heat-treated at 560℃ for 3h. After cooling to room temperature, the mixture was placed in a plasma generator. Oxygen and argon were mixed at a volume ratio of 6:5 as the working gas. Plasma treatment was performed for 15 min at a flow rate of 50 sccm and a radio frequency power of 75 W. The solution was then removed and added to 600 g of 91 wt% ethanol solution. The solution was ultrasonically dispersed at 80 W for 15 min. The pH was adjusted to 5 by adding 5 wt% acetic acid solution. 92 g of coating layer precursor solution was slowly added dropwise while stirring at 450 rpm. After the addition was complete, the solution was stirred at 300 rpm for 1.5 h, heated to 78 °C, refluxed at 150 rpm for 4 h, filtered, dried at 50 °C and 10 kPa for 5 h, and kept at 455 °C for 3.5 h. The solution was then cooled to room temperature to obtain modified glass fiber.

[0040] 184g of calcium oxide was slowly mixed with 760g of deionized water and stirred at 300rpm for 45min to obtain a calcium slurry. 192g of quartz powder (3μm particle size) was mixed with 750g of deionized water and stirred at 900rpm for 30min to obtain a silica slurry. 920g of calcium slurry, 922g of silica slurry, and 610g of deionized water were mixed and stirred at 1000rpm for 10min. 27g of modified glass fiber was slowly added while stirring at 700rpm. After addition, the mixture was stirred at 700rpm for 30min, filtered to remove water, and formed a green body. The green body was then steam-cured at 190℃ and 1.3MPa for 12h, dried at 130℃ for 8h, and cooled to room temperature to obtain a high-temperature resistant composite material for battery packs.

[0041] The present invention also includes comparative examples and related experiments.

[0042] Comparative Example 1 The difference between this comparative example and Example 3 is that acetylacetone was not added during the preparation of the barrier layer precursor solution. Instead, 73g of tetrapropoxide zirconium was slowly added dropwise under stirring at 500rpm. The remaining operation steps and reaction conditions were the same as in Example 3, resulting in a high-temperature resistant composite material for battery packs.

[0043] Comparative Example 2 The difference between this comparative example and Example 3 is that TEOS was not added during the preparation of the barrier layer precursor liquid. The remaining operation steps and reaction conditions are the same as in Example 3, resulting in a high-temperature resistant composite material for battery packs.

[0044] Comparative Example 3 The difference between this comparative example and Example 3 is that the modified glass fiber mixed with calcium slurry is replaced with an equal mass of glass fiber that has not been treated with the barrier layer precursor liquid, thus obtaining a high-temperature resistant composite material for battery packs.

[0045] Comparative Example 4 The difference between this comparative example and Example 4 is that a mixture of oxygen and argon gas was not used for plasma treatment. The remaining operation steps and reaction conditions are the same as in Example 4, resulting in a high-temperature resistant composite material for battery packs.

[0046] Mechanical property tests.

[0047] Referring to GB / T 5486 "Test Methods for Inorganic Rigid Thermal Insulation Products", the compressive strength of the high-temperature resistant composite material specimens prepared in each example and comparative example was determined under room temperature conditions. (MPa) The bottom surface of each specimen was heated to 800℃ in a thermal shock test furnace, held at that temperature for 30 minutes, and then allowed to cool naturally to room temperature to complete the thermal exposure of each specimen. The residual compressive strength of each specimen after thermal exposure was then measured. (MPa), according to the formula:

[0048] Calculate the compressive strength retention rate As shown in Table 1.

[0049] Table 1

[0050] Figure 1 The infrared spectrum of the modified glass fiber prepared in Example 4 is shown below. Figure 1 It can be seen that at a wavenumber of 1100 cm⁻¹ -1 The presence of strong characteristic peaks nearby indicates that the modified glass fiber surface is dominated by a continuous Si-O-Si bond network, at a wavenumber of 500 cm⁻¹. -1 The nearby characteristic peaks are relatively weak, indicating that the pre-coating liquid formed a coating layer outside the barrier layer, and this coating layer is mainly composed of Si-O-Si bonds; as shown in Table 1, compared with Examples 1 to 3, the high-temperature resistant composite materials (hereinafter referred to as composite materials) for battery packs prepared in Examples 4 to 6 have significantly improved performance. and The relatively large value indicates that by setting a coating layer outside the barrier layer, the mechanical interlock between the modified glass fiber and the matrix can be enhanced, the connection and expansion of microcracks in the matrix under thermal stress can be inhibited, and the compressive strength retention rate of the composite material after heat exposure can be improved.

[0051] Compared with Comparative Example 1, the composite material prepared in Example 3... and The relatively large value indicates that adding acetylacetone during the preparation of the barrier layer precursor solution is beneficial for forming a continuous barrier layer outside the glass fiber, reducing the alkali corrosion strength loss of the glass fiber, inhibiting the initiation and propagation of microcracks in the matrix under thermal stress, and improving the compressive strength retention rate of the composite material after heat exposure.

[0052] Figure 2 The infrared spectrum of the modified glass fiber prepared in Example 3 is shown below. Figure 2 It can be seen that at a wavenumber of 500cm -1 The presence of strong characteristic peaks nearby indicates that the surface of the modified glass fiber is dominated by Zr-O-Zr bonds, at a wavenumber of 960 cm⁻¹. -1 The presence of characteristic peaks nearby indicates that the modified glass fiber surface contains Zr-O-Si bonds, at a wavenumber of 1100 cm⁻¹. -1 The absence of obvious characteristic peaks nearby indicates that the modified glass fiber surface does not contain a continuous SiO2 phase, thus proving that the barrier layer precursor liquid formed a barrier layer outside the glass fiber. This barrier layer is mainly composed of Zr-O-Zr bonds and contains a small amount of Zr-O-Si bonds. Compared with Comparative Example 2, the composite material prepared in Example 3... The large values ​​of η and TEOS indicate that the addition of TEOS can introduce Zr-O-Si bonds into the barrier layer. After the silicon-oxygen components dissolve, the surface roughness of the barrier layer is improved, the mechanical interlock between the modified glass fiber and the matrix is ​​enhanced, the connection and expansion of microcracks in the matrix under thermal stress are suppressed, and the compressive strength retention rate of the composite material after heat exposure is improved.

[0053] Compared with Comparative Example 3, the composite material prepared in Example 3 has... The large values ​​of TEOS and η indicate that the barrier layer formed by the condensation of zirconium tetrapropoxide can effectively reduce the alkali corrosion strength loss of glass fibers, inhibit the breakage of glass fibers under thermal stress, and thus inhibit the initiation and propagation of microcracks in the matrix under thermal stress, thereby improving the compressive strength retention rate of the composite material after heat exposure.

[0054] Compared with Comparative Example 4, the composite material prepared in Example 4 has... and The larger value indicates that plasma treatment of the barrier layer using a mixture of oxygen and argon gases is beneficial for forming a coating layer outside the barrier layer, enhancing the mechanical interlock between the matrix and the modified glass fiber, and improving the compressive strength retention rate of the composite material after heat exposure.

Claims

1. A method for preparing a high-temperature resistant composite material for a battery pack, characterized in that, Includes the following steps: S1. Disperse glass fibers in an ethanol solution, adjust the pH value, add a barrier layer precursor solution, mix and react, dry and heat treat to obtain modified glass fibers. S2. Mix calcium slurry, silica slurry, deionized water and modified glass fiber, dehydrate to form a green body, then steam-press curing and drying to obtain a high-temperature resistant composite material for battery packs. The barrier layer precursor solution is prepared by mixing and reacting TEOS and acidic ethanol solution, then adding a zirconium-containing chelate solution and reacting to obtain the barrier layer precursor solution; the zirconium-containing chelate solution is prepared by reacting tetrapropionitrile and acetylacetone.

2. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 1, characterized in that, The barrier layer precursor solution is prepared by adding acetic acid solution dropwise to an 84-86 wt% ethanol solution to adjust the pH to 4-5, adding TEOS and reacting for 1-1.5 h, then slowly adding a zirconium-containing chelate solution under continuous stirring, and reacting for 40-50 min to obtain the barrier layer precursor solution; the zirconium-containing chelate solution is prepared by mixing and reacting tetrapropoxide zirconium and acetylacetone in an inert atmosphere for 30-40 min.

3. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 2, characterized in that, In step S1, glass fibers are dispersed in a 91-93 wt% ethanol solution, and acetic acid solution is added dropwise to adjust the pH to 4-5. The barrier layer precursor solution is slowly added under continuous stirring, and the reaction is carried out for 1-1.5 hours. The temperature is then raised to 78-80℃ and reacted for 3-4 hours. After filtration and vacuum drying, the mixture is heat-treated at 450-460℃ for 2-2.5 hours, then heat-treated at 550-560℃ for 3-4 hours, and finally cooled to obtain modified glass fibers. The zirconium content in the glass fibers is 14%-15%.

4. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 3, characterized in that, In step S1, after heat treatment at 550-560℃ for 3-4 hours and cooling, plasma treatment is performed using a mixture of oxygen and argon gas. Then, the mixture is dispersed in an ethanol solution, the pH value is adjusted, and a coating layer precursor solution is added for mixing and reaction. After drying and heat treatment, modified glass fiber is obtained. The coating layer precursor solution is prepared by mixing and reacting TEOS and acidic ethanol solution.

5. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 4, characterized in that, In step S1, oxygen and argon are mixed in a volume ratio of (1-1.2):1 and used as the working gas. After plasma treatment for 15-17 minutes under the conditions of working gas flow rate of 40-50 sccm and radio frequency power of 75-80W, the mixture is dispersed in a 91-93wt% ethanol solution. Acetic acid solution is added dropwise to adjust the pH value to 4-5. The coating layer precursor solution is slowly added under continuous stirring and reacted for 1-1.5 hours. The temperature is raised to 78-80℃ and reacted for 3-4 hours. The mixture is filtered, dried under reduced pressure, and then heat-treated at 450-460℃ for 3-4 hours. After cooling, modified glass fiber is obtained.

6. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 4, characterized in that, The coating layer precursor solution is prepared by adding acetic acid solution dropwise to an 84-86 wt% ethanol solution to adjust the pH to 4-5, adding TEOS and reacting for 2-2.5 h to obtain the coating layer precursor solution.

7. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 1, characterized in that, In step S2, calcium slurry, silica slurry, modified glass fiber and deionized water are mixed and pressed into a blank. The blank is then steam-cured at 190-195℃ and 1.3-1.4MPa for 12-14 hours, dried at 130-140℃ for 6-8 hours, and cooled to obtain a high-temperature resistant composite material for battery packs.

8. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 7, characterized in that, The calcium slurry is prepared by reacting calcium oxide with deionized water, and the silica slurry is prepared by mixing quartz powder with deionized water.

9. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 8, characterized in that, The high-temperature resistant composite material for the battery pack comprises the following raw materials in parts by weight: 910-920 parts of calcium slurry, 918-925 parts of silica slurry, 600-610 parts of deionized water, and 27-30 parts of modified glass fiber; the modified glass fiber comprises the following raw materials in parts by weight: 50-60 parts of glass fiber and 190-195 parts of barrier layer precursor liquid.

10. The method for preparing a high-temperature resistant composite material for a battery pack according to claim 9, characterized in that, The calcium slurry is prepared by mixing and reacting 180-184 parts by weight of calcium oxide and 750-760 parts by weight of deionized water; the silica slurry is prepared by mixing 188-192 parts by weight of quartz powder and 745-755 parts by weight of deionized water; the barrier layer precursor liquid comprises the following raw materials in parts by weight: 73-77 parts of zirconium tetrapropoxide, 49-52 parts of acetylacetone, 7-8 parts of TEOS, and 140-150 parts of 84-86 wt% ethanol solution; the modified glass fiber further comprises 90-95 parts by weight of coating layer precursor liquid, which comprises the following raw materials in parts by weight: 30-35 parts of TEOS and 80-90 parts of 84-86 wt% ethanol solution.

Citation Information

Patent Citations

  • Process for preparing lightweight high temperature resistance xonotlite calcium silicate insulation material

    CN104250089A